Genomic identification of recipient-derived hepatocytes in liver transplantation: a hypothesis linking graft repopulation to immune tolerance - Kim, Seoung Hoon (Frontiers in Immunology, 2025)
BackgroundOperational tolerance, defined as stable liver graft function without immunosuppression, has been observed in select transplant recipients. While immune regulatory mechanisms have been implicated, the biological processes underlying tolerance remain incompletely understood. Notably, recipient-derived hepatocytes have been shown to progressively repopulate donor livers, raising the possibility that this histological change may contribute to tolerance induction.HypothesisThis hypothesis suggests that progressive replacement of donor hepatocytes by recipient-derived cells reduces donor alloantigen exposure, thereby attenuating allo-immune responses and enabling stable graft acceptance without pharmacologic immunosuppression. This phenomenon could be detected through Y-chromosome–specific assays in sex-mismatched transplants or via donor-recipient genomic profiling in all cases.Supporting evidenceThe liver’s intrinsic regenerative capacity permits continuous hepatocyte turnover and engraftment of recipient-derived cells, particularly under conditions of chronic low-grade injury. Clinical reports have documented the presence of recipient-derived hepatocytes in liver allografts, and operational tolerance has been associated with decreased donor-derived cell-free DNA and reduced allo-immune activation. Although techniques such as FISH and qPCR targeting the Y-chromosome are effective in sex-mismatched cases, broader applicability requires STR or SNP-based genotyping. Integrating these genetic approaches with hepatocyte-specific methylation or transcriptomic profiling may significantly improve the accuracy and clinical relevance of recipient-derived hepatocyte detection.ImplicationsThis hypothesis, if validated, could shift the conceptual model of transplant tolerance from solely immune regulation to a dynamic process of histological replacement. It may also lead to biomarker-driven strategies for immunosuppression withdrawal support novel diagnostic approaches to confirm operational tolerance in appropriate candidates.